Intercalation of a molybdenum eta(3)-allyl dicarbonyl complex in a layered double hydroxide and catalytic performance in olefin epoxidation - Gomes, Ana C.
A Zn-Al layered double hydroxide (LDH) intercalated by [Mo(eta(3)-C3H5)Cl(CO)(2)(bpdc)](2-) anions (bpdc = 2,2'-bipyridine-5,5'-dicarboxylate) has been prepared by coprecipitation from aqueous solution and characterised by various techniques. The one-pot method gives rise to a highly organised intercalate with an interlayer spacing of 18.3 angstrom and up to six (00l) basal reflections in the powder X-ray diffraction pattern. Spectroscopic studies (FT-IR, FT-Raman, C-13 CP MAS NMR and UV-Vis) confirm the presence of structurally intact [Mo(eta(3)-C3H5)Cl(CO)(2)(bpdc)](2-) anions. The interlayer spacing of 18.3 angstrom indicates that the material contains a monolayer of guest anions positioned in such a way that the bpdc ligands are arranged with their longest dimension roughly perpendicular to the hydroxide layers of the host. Thermal properties were studied by thermogravimetric analysis and differential scanning calorimetry. The intracrystalline reactivity of intercalated dicarbonyl complexes was probed by using the hybrid nano-composite as a precatalyst in the liquid phase epoxidation of cis-cyclooctene with tert-butylhydroperoxide as oxidant. Under the reaction conditions used, oxidative decarbonylation of the guest molecules takes place (with release of CO and CO2 as confirmed by on-line gas chromatography experiments) to give intercalated molybdenum oxide/bipyridine species that selectively catalyse the epoxidation reaction. The intracrystalline oxidative decarbonylation reaction is topotactic in nature.